Toward More Effective Risk Disclosure for Technology-Enhanced Investing - Donald C. Langevoort (Washington University Law Quarterly, 1997)
I will turn first to consider the promise of technology-enhanced investing and the concerns that might heighten. Then, I propose a significant modification of the mandatory disclosure obligation as it relates to investment risk.
Keywords: Electronic trading of securities